A high yielding semi-dwarf dicoccum wheat - Nilgiri Khapli (HW 1098) released for cultivation to dicoccum growing areas of India - M, Sivasamy; Kumar, Jagdish; Jayaprakash, P; Vikas, V K; ., Vinod; Kumar, Sanjay; Singh, G P; Sharma, R K; Yadav, Rajbir; Sharma, J B; Prabhu, K Vinod; Bhagwat, S G; et al. (Journal of Cereal Research, 2014)
A new high yielding, disease resistant semi-dwarf Triticum dicoccum wheat variety HW 1098(Nilgiri Khapli) has been released by Central Sub-committee on crop standards and notifcations and release of variety for agricultural crops to all the dicoccum growing zones in India under timely sown irrigated conditions during 2013. It has mean grain yield of 45.53q ha-1 with maximum yield potential of 47.8q ha-1 , recording relatively lesser yield loss under late sown conditions when compared to checks. The variety has sown high degree of adult plant resistance against all the three rust under feld conditions and SRT data indicated resistance response to all the pathotypes of brown, stem rust and to all yellow rust pathotypes except race 78S84(Mixed reaction). HW 1098 a mutant possesses at par quality with NP 200 a traditional dicoccum variety with high protein(16.5%) higher grain weight(46.5g), sedimentation value(29.0ml) and higher Î²-carotene(3.39ppm) and having an ideal plant height(85cm)